2008
DOI: 10.1038/ijir.2008.23
|View full text |Cite
|
Sign up to set email alerts
|

Women's sexual function and dysfunction: current uncertainties, future directions

Abstract: There is increasing evidence that women at the outset of sexual activity do not need to have sexual desire, as in 'drive', and that many do not distinguish desire from arousal. Multiple modes of investigation confirm poor correlation between women's subjective arousal and measured genital congestion. Suggested revisions to the DSM-IV definitions of sexual disorder have been published: there is now need to align interview assessments and screening questionnaires with contemporary understanding of women's sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 108 publications
(117 reference statements)
1
63
0
6
Order By: Relevance
“…First, more care is needed in interpreting how other facets of female sexual experience might relate to desire (Basson, 2008;Levine, 2003). While arousal, lubrication, frequency of sex/orgasm, and satisfaction may be motivationally interlinked and underpinned by the degree of current attraction to the woman's partner, autosexual behavior may be motivationally distinct and perhaps inversely related with partner attraction.…”
Section: Future Directionsmentioning
confidence: 99%
“…First, more care is needed in interpreting how other facets of female sexual experience might relate to desire (Basson, 2008;Levine, 2003). While arousal, lubrication, frequency of sex/orgasm, and satisfaction may be motivationally interlinked and underpinned by the degree of current attraction to the woman's partner, autosexual behavior may be motivationally distinct and perhaps inversely related with partner attraction.…”
Section: Future Directionsmentioning
confidence: 99%
“…Some of the literature has suggested that diagnostic frameworks that rely on direct physical measurement of sexual dysfunction are not very reliable, which has led to the use of self-report scales. These inventories have become indispensable tools in clinical and research programs, 19,20 which is why we relied on a self-report questionnaire for this study. We also explored whether any demographic variables were associated with sexual functioning among women post-hemorrhoidectomy.…”
mentioning
confidence: 99%
“…A mulher vivencia sua sexualidade de forma peculiar nos diversos períodos de sua vida 1 , especialmente durante a gestação, quando pode ter sua função sexual e qualidade de vida comprometidas. Somente o fato de tomar conhecimento da gravidez, logo nas primeiras semanas, parece afetar a atividade sexual feminina, diminuindo o número de coitos 2 .…”
Section: Introductionunclassified